KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP N 7 KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Nurul Hidayanti; Auzar Auzar; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study examines the ability to write text description of class VII students of SMP N 7 of Bukit Batu Sub-district, Bengkalis Regency. The purpose of this study is to describe the ability to write text description of students of class VII SMP N 7 Bukit Batu Sub-District Bengkalis. This study has a population of 31 and a sample of 29. The results of research when tested using t test is the ability to write text description of students class VII equal to the value of comparison. The comparison scores applied in this study were 20. The students' writing ability was the same as the comparator score. In other words the hypothesis is accepted. This means the ability to write a text description of students of class VII SMP N 7 Bukit Batu District Bengkalis relatively low.Keywords: Ability, Writing, Description Text